Методи забезпечення анонімності користувача в мережі інтернет - Папазов, К. О. (ХНУРЕ, 2024)
This paper examines the different methods of providing user anonymity in the Internet, including proxy servers, virtual private networks (VPN) and Onion routing. The paper evaluates and compares these methods according to the criteria of anonymity level, speed, cost and ease of use. The paper also discusses the advantages and disadvantages of each method, as well as the specific needs of users. The paper concludes that VPNs are the “golden mean” that offer a balance between anonymity, internet connection speed and technical complexity. However, the choice of a particular method depends on the user’s preferences and goals.
Keywords: забезпечення анонімності користувача; user anonymity